High strength and high conductivity pure copper prepared by ECAP-Conform combined with cryogenic rolling and recrystallization annealing - Yuehong Zheng; Jianan Niu; Ying Lu; Shipeng Xu; Zhumin Li; He Zhao; Peiqing La (Journal of Materials Research and Technology)
The large-scale production of high-strength and high-conductivity pure copper holds significant importance for electronic information and transportation fields. This study innovatively proposes a composite thermomechanical processing route of “ECAP-C + cryogenic rolling + recrystallization annealing”, aiming to significantly improve material strength while maintaining excellent electrical conductivity. The research demonstrates that through precise regulation of grain size and internal defects (primarily dislocations), pure copper achieves both high electrical conductivity (91.9 %IACS) and remarkably enhanced tensile strength (506.38 MPa) with elongation (9.8 %). Microstructural characterization reveals refined average grain size (0.85 μm) and optimized dislocation density (1.07 × 1015 m−2), which exhibit weaker electron scattering compared to solute atoms while substantially improving grain refinement strengthening and dislocation strengthening effects. This study applies the material simplification concept and non-alloying strengthening strategies to develop high-performance pure copper, proposing a scalable composite processing technology that conserves resources. It provides novel strategies and perspectives for developing other high-strength, high-conductivity materials.